Green roof simulator with native and exotic plant species - Perillo, Vanesa Liliana (2024)
The rise of urban greenhouse gas emissions creates the need to improve available mitigation strategies. The effectiveness of green roofs depends on their correct design, including vegetation choice. To this aim, we studied the performance of native and exotic plants in hydric deficit conditions of a semi-arid urban area, Bahía Blanca, Argentina, and their ability to sequester CO2. Three native (Poa lanuginosa, Sphaeralcea australis, and Phyla nodiflora) and three exotic (Oscularia deltoides, Sedum ´tokyo sun´, and Sedum nussbaunerianum) species were tested in an extensive green roof simulator with no irrigation. Exotics Oscularia deltoides and Sedum nussbaunerianum did not survive the fall, while Sedum ´tokyo sun´ survived until late spring. All native plants survived, but their growth was affected by the hydric deficit of the warmer months. Seasonal CO2 fluxes were detected, with the most C sequestration in the colder months. Warmer months had the highest CO2 release. Native Poa lanuginosa sequestered 2.2 times more CO2 than exotic Sedum ´tokyo sun´ and native Phyla nodiflora, showing that C sequestration depends on plant type and not hydric-deficit adaptation. Construction of extensive green roofs in semi-arid cities requires the use of native plants that can withstand large hydric deficits.